Hidden reserves as an alternative channel of firm finance - İbrahim Yarba (Central Bank Review (CBR), 2021)
This study analyses the argument that whether Turkish non-financial firms utilize any informal source of alternative funding during economic uncertainties over the last decade. This study is the first to explore the issue and provide some insights regarding how small and medium-sized enterprises do react to the financial constraint problem in such an economic environment. Both trend analysis and empirical panel model estimations provide supporting evidence that Turkish non-financial firms have some reserves (e.g., owners', relatives' and/or friends' personal wealth) that are utilized during the times of persistent stress and tightening of macroprudential policies. Most strikingly, this is the case for only small and medium-sized enterprises but not for large firms.
Keywords: C23; D21; D81; G18; G32; 330; Alternative firm financing channels; Hidden reserves; Macroprudential policy; Uncertainty